Aśvaghoṣa and His Canonical Sources (III): The Night of Awakening (Buddhacarita 14.1–87). - Eltschinger, Vincent (Journal of Indian Philosophy, 2019)
The present paper is the third in a series dedicated to uncovering the canonical sources of Aśvaghoṣa's Buddhacarita and, to the extent possible, the monk-poet's sectarian affiliation. Whereas parts I and II focused on Chapter 16's indebtedness to (Mūla)sarvāstivāda Vinaya and/or Sūtra literature, this third part inquires into the sources of Aśvaghoṣa's account of the Buddha's enlightenment in Chapter 14 (whose first 31 verses have been preserved in their Sanskrit original). Detailed analysis reveals this chapter's intimate relationship with T. 189, a (Mūla)sarvāstivāda (?) biographical sūtra extant in Chinese translation only, but also with textual materials that have come to belong to Mūlasarvāstivāda literature and, as already demonstrated by Kajiyama Yūichi, with the Nagar(opam)asūtra of the Saṃyuktāgama. Among these likely sources, some provide a lively description of the five destinies, others relate to the iconographic prescriptions laid down for drawing the so-called Wheel of saṃsāra/existence, while yet others spell out the doctrine of dependent origination. The detailed comparison of these materials is followed by an admittedly speculative attempt to assess the relationship between these sources.